Usefulness of the 6-minute walk test as a screening test for pulmonary arterial enlargement in COPD - Oki Y; Kaneko M; Fujimoto Y; Sakai H; Misu S; Mitani Y; Yamaguchi T; Yasuda H; Ishikawa A (International Journal of COPD, 2016)
Yutaro Oki,1,2 Masahiro Kaneko,3 Yukari Fujimoto,1 Hideki Sakai,2 Shogo Misu,1,2 Yuji Mitani,1,4 Takumi Yamaguchi,1,2 Hisafumi Yasuda,1 Akira Ishikawa1 1Department of Community Health Sciences, Kobe University Graduate School of Health Sciences, 2Department of Rehabilitation, 3Department of Respiratory Medicine, Kobe City Medical Center West Hospital, Kobe, 4Department of Rehabilitation, Sapporo Nishimaruyama Hospital, Sapporo, Japan Purpose: Pulmonary hypertension and exercise-induced oxygen desaturation (EID) influence acute exacerbation of COPD. Computed tomography (CT)-detected pulmonary artery (PA) enlargement is independently associated with acute COPD exacerbations. Associations between PA to aorta (PA:A) ratio and EID in patients with COPD have not been reported. We hypothesized that the PA:A ratio correlated with EID and that results of the 6-minute walk test (6MWT) would be useful for predicting the risk associated with PA:A >1.Patients and methods: We retrospectively measured lung function, 6MWT, emphysema area, and PA enlargement on CT in 64 patients with COPD. The patients were classified into groups with PA:A ≤1 and >1. Receiver-operating characteristic curves were used to determine the threshold values with the best cutoff points to predict patients with PA:A >1.Results: The PA:A >1 group had lower forced expiratory volume in 1 second (FEV1), forced vital capacity (FVC), FEV1:FVC ratio, diffusion capacity of lung carbon monoxide, 6MW distance, and baseline peripheral oxygen saturation (SpO2), lowest SpO2, highest modified Borg scale results, percentage low-attenuation area, and history of acute COPD exacerbations ≤1 year, and worse BODE (Body mass index, airflow Obstruction, Dyspnea, and Exercise) index results (P<0.05). Predicted PA:A >1 was determined for SpO2 during 6MWT (best cutoff point 89%, area under the curve 0.94, 95% confidence interval 0.88–1). SpO2 <90% during 6MWT showed a sensitivity of 93.1, specificity of 94.3, positive predictive value of 93.1, negative predictive value of 94.3, positive likelihood ratio of 16.2, and negative likelihood ratio of 0.07.Conclusion: Lowest SpO2 during 6MWT may predict CT-measured PA:A, and lowest SpO2 <89% during 6MWT is excellent for detecting pulmonary hypertension in COPD. Keywords: 6-minute walk test, chronic obstructive pulmonary disease, exercise-induced oxygen desaturation, pulmonary artery